Digital Multimedia in the form of an Android-based e-module - Ikhsan Ikhsan; Isnardi Isnardi; Novinaldi Novinaldi; Ahmad Fikri Fajri; Ade Putra Nanda (Jurnal Mandiri IT, 2023)
In general, the purpose of this e-module is to limit the use of paper in making learning modules that are appropriate to the teaching material, and the specific goal is how to make learning material packaged in an attractive form. The most fundamental problem is that students are not interested in learning by using modules in text form, plus they prefer applications on smartphones, especially Android. However, most books and modules can be read through the gadget in pdf or epub format. However, from the children's point of view, it would be more interesting if it was packaged in digital multimedia that involved animation and sound. This research was built using the Luther Sutopo method, which involved six stages. The results of the research are digital module applications based on Android. Testing of this e-module application was conducted on several elementary school children, with 90% results being able to do the quiz correctly.